Optimization of Extraction Conditions for Determination of Tiliroside in Tilia L. Flowers Using an LC-ESI-MS/MS Method - Aleksandra Pieczykolan; Wioleta Pietrzak; Renata Nowak; Józefina Pielczyk; Karolina Łamacz (Journal of Analytical Methods in Chemistry)
Tiliroside exhibits a wide spectrum of effects on the human body; considering expensive synthesis of tiliroside, linden trees seem to be a good source of this compound. For the first time, 46 various extraction methods were developed to receive tiliroside from Tilia L., including ultrasound-assisted extraction, maceration, maceration with stirring, accelerated solvent extraction, and extraction under reflux. The effects of extraction techniques, solvents, additives, and temperature on the content of tiliroside were studied using analytical and statistical methods. A new, rapid, simple, sensitive, and selective liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) method was developed to determine the content of tiliroside in Tilia L. flowers. The LC-ESI-MS/MS analysis demonstrated the highest content of tiliroside in Tilia L. flowers obtained using accelerated solvent extraction (ASE) where 70% ethanol with addition of 1% acetic acid was used as a solvent (7.400 ± 0.019 mg of tiliroside per g dry extract).The results showed that the extracts of Tiliae inflorescentia contained large amounts of tiliroside; therefore, they are good sources of this compound. Moreover, ASE was found to be superior to other extraction techniques due to its high efficiency as well as considerable saving of time and solvent.